Peran pendidikan karakter berbasis perennialisme dalam mempersiapkan mahasiswa bermoral dimasa depan - Sabrina Ais Zahra; Abdul Khobir; Ahmad Makhasin Ma’arif; M. Irfansyah Afsalu Ramedhon (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
Character education based on perennialist thought holds an important position in shaping students with integrity amid the development of the digital era and globalization. Universal values such as truth, goodness, and beauty serve as the main foundation in strengthening ethics. This study uses a library research method with a descriptive qualitative approach. The main data used come from books, scientific journals, articles, and official documents, particularly those discussing character education and perennialism. The data analysis stages are as follows: first, data reduction; second, organizing information; third, drawing conclusions. The results show that the perennialist approach is able to prioritize student ethics and character so that they understand and apply these values in their lives. This implementation can be carried out through several educational efforts such as the curriculum, guidance and advice from educators, the provision of morally valuable activities within the school environment, as well as good social interactions. Of course, instilling morals from an early age is very necessary, so that these attitudes develop gradually and are better understood by children as preparation for their future. Therefore, prioritizing morals is very necessary, especially in today’s era, which is rife with various moral issues faced by students in higher education. With character education, a generation will emerge that is not only highly educated but also morally upright.